(3GdeWhds - (3GdJaJGRGfj, SYO GdOjf, eSYhO Hf YeQ Hf YHO Gddg, J (B793(3g`s ((3eMehO Hf jhSas)
(3ChdgG (B:s
(3GdMeO ddg GdPj CdgefG MbGFb GdeYGfj(B...(3hHYO aEf CMb GdaVGFd HGdJbOje(B... (3aEfg cTGa Yf MbGFb GdJfRjd(B...s
(3BNQgG (B:s
(3hGdJPcQ ddCMcGe GdePchQI aj aj Yde GdeYGfj hGdHjGf hEf dcd ebGe ebGdG dG jMSf ajg ZjQg hdG jbhe ebGeg ZjQg(B... (3gPG BNQ eG CQOfG LeYgs
(3HChdgG agQSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B7(3, U(B217s
(3cTa GdXfhf(B: (3L(B2(3, U(B1722s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdHdGZIs